Role of p63 and p73 isoforms on the cell death in patients with hepatocellular carcinoma submitted to orthotopic liver transplantation. - Raúl González; Ángel J De la Rosa; Alessandro Rufini; María A Rodríguez-Hernández; Elena Navarro-Villarán; Trinidad Marchal; Sheila Pereira; Manuel De la Mata; Martina Müller-Schilling; Juan M Pascasio-Acevedo; María T Ferrer-Ríos; Miguel A Gómez-Bravo; et al. (PLoS ONE, 2017)
Patients with hepatocellular carcinoma (HCC) submitted to orthotopic liver transplantation (OLT) have a variable 5-year survival rate limited mostly by tumor recurrence. The etiology, age, sex, alcohol, Child-Pugh, and the immunesuppressor have been associated with tumour recurrence. The expression of ΔNp73 is related to the reduced survival of patients with HCC. The study evaluated the expression of p63 and p73 isoforms and cell death receptors, and their relation to tumour recurrence and survival. The results were in vitro validated in HCC cell lines.HCC sections from patients submitted to OLT were used. The in vitro study was done in differentiated hepatitis B virus (HBV)-expressing Hep3B and control HepG2 cells. The expression of cell death receptors and cFLIPS/L, caspase-8 and -3 activities, and cell proliferation were determined in control and p63 and p73 overexpressing HCC cells.The reduced tumor expression of cell death receptors and TAp63 and TAp73, and increased ΔNp63 and ΔNp73 expression were associated with tumor recurrence and reduced survival. The in vitro study demonstrated that HBV-expressing Hep3B vs HepG2 cells showed reduced expression of p63 and p73, cell death receptors and caspase activation, and increased cFLIPL/cFLIPS ratio. The overexpression of TAp63 and TAp73 exerted a more potent pro-apoptotic and anti-proliferative effects in Hep3B than HepG2-transfected cells which was related to cFLIPL upregulation.The reduction of TAp63 and TAp73 isoforms, rather than alteration of ΔN isoform expression, exerted a significant functional repercussion on cell death and proliferation in HBV-expressing HepB cells.